Application of Numerical Methods in Engineering Problems Using MATLAB® - Al-Furjan, M. S. H.; Bidgoli, M. Rabani; Kolahchi, R.; Farrokhian, A.; Bayati, M. R. (Emerging materials and technologies, 2023)
Application of Numerical Methods in Engineering Problems using MATLAB® presents an analysis of structures using numerical methods and mathematical modeling. This structural analysis also includes beam, plate, and pipe elements, and also examines deflection and frequency, or buckling loads. The various engineering theories of beams/plates/shells are comprehensively presented, and the relationships between stress and strain, and the governing equations of the structure are extracted. The book explains numerical methods based on derivatives, especially the differential quadrature method.